Moral Hazard and the Internal Organization of Joint Research - Simona Fabrizi; Steffen Lippert (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2004)
Lecture on the first SFB/TR 15 meeting, Gummersbach, July, 18 - 20, 2004: We address the question of how the internal organization of partnerships can be affected by moral hazard behavior of their division(s)/agent(s). We explore cases where two entregreneurs, each employing one agent subject ot moral hazard, decide how to conduct a research project together. The project's success probability is affected by agent(s)' effort(s). A joint entity can take two configurations: either both, or only one agent is kept. If two agents are kept, all degrees of substitutability between agents' efforts are considered. We show that the privately optimal internal organization of the joint entity is also socially optimal, except when agents' efforts just start to duplicate each other. In this range, due to moral hazard, too few parterships keeping both agents occur as compared to what would be socially optimal. A restriction on the number of agents to be kept in a partnership would induce too few of them leading to socially worse outcomes.
urn:nbn:de:bvb:19-epub-13530-3
Keywords: D21; D23; L23; 330; internal organization of partnerships; moral hazard; efforts' interactions; cost functions